The long-term impact of resilience-building interventions in nurses: A review of the evidence - Karanikola, Maria; Kyranou, Maria (My University, 2024)
The purpose of the study was to provide data on the long-term impact of resilience interventions in nurses as measured via RCTs. Only four studies included long-term follow-up assessments after resilience-building interventions. In two of the studies longer duration treatment was employed (8 or 12 weeks). The other two studies used shorter interventions such as a 90 min duration lecture on stress and resilience or a 3-hour sensory awareness class. There is preliminary evidence that resilience demonstrated improvements 3 months after the intervention even when there was no improvement right after the implementation. These findings imply that time might be a critical component for the resilient response to develop, and that intervention studies need to plan for multiple follow-up assessments. Furthermore, the conclusions of the review aim to draws attention to the conceptual definition of resilience as an outcome compared to the previous of resilience as a characteristic of the individual (trait).
Keywords: Resilience; Longitudinal; Nursing; Interventions